2016
DOI: 10.1007/s10461-016-1410-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PREPARE, a Multi-component, School-Based HIV and Intimate Partner Violence (IPV) Prevention Programme on Adolescent Sexual Risk Behaviour and IPV: Cluster Randomised Controlled Trial

Abstract: Young South Africans, especially women, are at high risk of HIV. We evaluated the effects of PREPARE, a multi-component, school-based HIV prevention intervention to delay sexual debut, increase condom use and decrease intimate partner violence (IPV) among young adolescents. We conducted a cluster RCT among Grade eights in 42 high schools. The intervention comprised education sessions, a school health service and a school sexual violence prevention programme. Participants completed questionnaires at baseline, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 28 publications
1
109
0
4
Order By: Relevance
“…Of the five school‐level environment interventions, three employed teams of school staff and students to improve school policies or practices addressing school climate or to improve safety and prevent sexual violence . Two interventions provided teachers with knowledge and skills related to classroom management and interactive teaching or to strategies to support actions recommended by school teams .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the five school‐level environment interventions, three employed teams of school staff and students to improve school policies or practices addressing school climate or to improve safety and prevent sexual violence . Two interventions provided teachers with knowledge and skills related to classroom management and interactive teaching or to strategies to support actions recommended by school teams .…”
Section: Resultsmentioning
confidence: 99%
“…Only one meta‐analysis was possible for outcomes of school‐environment studies. Three randomized trials reported intervention effects on sexual debut and were included in the meta‐analysis. The first trial, the Gatehouse Project, involved 25 secondary schools in Australia and reported on sexual debut (i.e., whether students had ever had sexual intercourse) among three cross‐sectional samples of eighth‐grade students at two and four years after baseline .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent large-scale trials covering wide geographical areas in the United Kingdom [4649], South Africa [50] and Switzerland [51] have encouraged us to design and conduct a nation-wide cluster randomised clinical trial to test the effects of user-centred and collaborative intervention to prevent and decrease coercive events in psychiatric hospitals. Contrary experiences of the impact of large-scale intervention trials also exist.…”
Section: Introductionmentioning
confidence: 99%